2013
DOI: 10.1021/pr301222b
|View full text |Cite
|
Sign up to set email alerts
|

Toward Personalized Nutrition: Comprehensive Phytoprofiling and Metabotyping

Abstract: Nutrition research is increasingly concerned with the complex interactions between multicomponent dietary ingredients and the human metabolic regulatory system. The substantiation of nutritional health benefits is challenged by the intrinsic complexity of macro- and micronutrients and individualized human metabolic responses. Metabonomics, uniquely suited to assess metabolic responses to deficiencies or excesses of nutrients, is used to characterize the metabolic phenotype of individuals integrating genetic po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 110 publications
0
17
0
Order By: Relevance
“…This study highlighted markers related to the ingestion of herbs and demonstrated the potential of such an approach in this emerging field. To date, and despite the rapid development of systems biology only a few studies have been published, but comprehensive approaches that combine phytoprofiling and metabotyping are now emerging (Xie et al 2013). From a clinical perspective, systems biology approaches guided by Chinese medicine have revealed new markers for sub-typing rheumatoid arthritis patients (van Wietmarschen et al 2009) and similar strategies have also been applied for studying effects of TCM for complex diseases.…”
Section: Pro-drugs In Natural Product Extractsmentioning
confidence: 99%
“…This study highlighted markers related to the ingestion of herbs and demonstrated the potential of such an approach in this emerging field. To date, and despite the rapid development of systems biology only a few studies have been published, but comprehensive approaches that combine phytoprofiling and metabotyping are now emerging (Xie et al 2013). From a clinical perspective, systems biology approaches guided by Chinese medicine have revealed new markers for sub-typing rheumatoid arthritis patients (van Wietmarschen et al 2009) and similar strategies have also been applied for studying effects of TCM for complex diseases.…”
Section: Pro-drugs In Natural Product Extractsmentioning
confidence: 99%
“…Metabonomics, or assessment of metabolic responses based on nutrient sufficiency or deficiency, is a way to characterize the metabolic phenotype of individual and predict their corresponding interactions with gut microbiota, environment, and behavior. In addition, Xie et al [10] discuss advances in the role of phytochemical modulation of cellular physiology and propose phytochemical profiling, or phytoprofiling, to assist in the facilitation of determining phytonutrient requirements with more effective interventions with plant-derived compounds. Hence, the needs of the individual can be complex and require in-depth assessment before interventions can be confidently applied.…”
Section: The Emergence Of Science To Support Personalized Nutritiomentioning
confidence: 99%
“…1234 Mass spectrometry (MS) and nuclear magnetic resonance (NMR) spectroscopy are the two leading analytical methods in metabolomics. 5 This is because of their high-resolution power allowing detection of hundreds of signals from individual metabolites without the need of extensive sample purification or hyphenation.…”
Section: Introductionmentioning
confidence: 99%